Formation of a Communicative Canon: (Based on the Material of the Bureaucratic Documentation of the VAPP – RAPP – Organizing Committee of the SSP of the Ussr) (London Journal of Research In Humanities and Social Sciences, 2024)
The article is devoted to the problem of understanding the impact of bureaucratic documentation (informational, instructional, circular letters and others) on the communication of literary organizations (from the center to local organizations). The VAPP, which separated from it in May 1928, was taken as a literary institution, and the Organizing Committee of the Union of Soviet Writers, formed by the Resolution of the Organizing Bureau of the Central Committee of the CPSU(b) dated May 7, 1932 “On measures to implement the resolution of the Politburo of the Central Committee of the CPSU (b) “On the Restructuring of literary and Artistic Organizations”, the Organizing Committee of the Union of Soviet Writers.
Keywords: discourse markers; shell noun; causal relation; Problem-Solution; clause-relational approach; Mobility; Southwestern Europe; Struma River Valley; Neolithization; Early Neolithic; Dilemma-based learning; Gamification; 3rd Junior High School Literature.; Epistolary; instructional letter; circular letter; "Strikers in literature"; literary institution; VAPP; RAPP; Organizing Committee of the SSP of the USSR; M. Gorky